The Relationship between Finance and Knowledge with the Performance of Health Workers based on the Malcom Baldrige Criteria in the Kendari City Hospital Inpatient Unit - Ruliyati, Lilis; Saafi, La Ode; Tasnim, Tasnim (Waluya The International Science of Health Journal, 2024)
Introduction:A preliminary survey conducted showed that there were health workers who had poor attitudes and personalities in providing services. Apart from that, his ability and work experience do not guarantee that he can provide satisfaction to patients. The aim of this research is to analyze the relationship between finances and knowledge and the performance of health workers based on the Malcom Baldrige criteria in the Kendari City Hospital Inpatient Unit. Method:This research is quantitative using a Cross Sectional Study design, with a population of 101 people and a sample of 81 respondents using the Cluster Random Sampling technique. Result:The chi square statistical test at the 95% confidence level (α=0.05) shows that the p value = 0.001 because Ho is rejected or Ha is accepted, which means there is a relationship between finances and performance and the chi square statistical test is at the 95% confidence level (α=0 .05) shows that the p value = 0.001 because Ho is rejected or Ha is accepted, which means there is a relationship between knowledge and the performance of health workers at the Kendari City Hospital Inpatient Unit. Conclusion: There is a relationship between Finance and Knowledge and the Performance of Health Workers based on the Malcom Baldrige Criteria in the Kendari City Hospital Inpatient Unit.